2020
DOI: 10.24875/gmm.20005384
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitución de células natural killer después del trasplante de células progenitoras hematopoyéticas en niños

Abstract: Introducción: Después de un trasplante de células progenitoras hematopoyéticas (TCPH), la reconstitución de las células natural killer (NK) es la principal barrera contra las infecciones virales. Objetivo: Determinar que el conocimiento sobre la cinética de la reconstitución de las células NK posterior al TCPH contribuye a un eficiente monitoreo del trasplante, lo que incrementa la posibilidad de éxito de este. Método: Se incluyeron 21 pacientes sometidos a TCPH, así como un grupo control de individuos clínica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…2). In the study conducted by Parra et al, it was reported that patients with HSCT achieve a late immune reconstitution, having an adequate cellular number up to 2 years after transplantation; however, no association with a more significant number of infections was observed 33 .…”
Section: Discussionmentioning
confidence: 95%
“…2). In the study conducted by Parra et al, it was reported that patients with HSCT achieve a late immune reconstitution, having an adequate cellular number up to 2 years after transplantation; however, no association with a more significant number of infections was observed 33 .…”
Section: Discussionmentioning
confidence: 95%